Secondary School Student Mobility: Social and Cultural Capital Transmission Through Merit-based Exchange Programs (Comparative & International Education Series, 2021)
The last decade has seen a significant increase of International Student Mobility (ISM) and a growing popularity of secondary school exchange programs in the US and around the world. Drawing upon theories of social and cultural capital, the purpose of this study is to explore equity issues in secondary school student mobility. This qualitative study utilized semi-structured interviews to unpack transnational experiences of alumni of two merit-based exchange programs, the Future Leaders Exchange (FLEX) and the Kennedy Lugar Youth Exchange and Study (YES). Findings show that even short-term ISM in the form of merit-based programs might tap into further transmission of not only social and cultural capital but also participants’ symbolic and mobility capital. Keywords: Alumni, cultural capital, exchange programs, intercultural exchange, international student mobility, secondary school education, social capital